The evolving paradigm of the subauroral geospace - Mishin, Evgeny V. (Frontiers in Astronomy and Space Sciences, 2023)
An assessment is given of the status quo of fast subauroral flows -- subauroral ion drifts (SAID) and subauroral polarization streams (SAPS). For a few decades, their development has been interpreted in terms of the voltage and current magnetospheric generators based largely on the drift motion of test particles. Recent multispacecraft observations revealed serious flaws of the generator paradigm and called for a new generation mechanism of fasttime subauroral flows and ring current (RC) injections. A novel model includes them into the overarching problem of penetration of magnetotail plasma flow bursts (MPFs) into the plasmasphere and the substorm current wedge (SCW) development. SAID are created near the plasmapause where inbound MPFs are short-circuited by the cold plasma. This stops the MPF’s electrons and forms the “dispersionless” plasma sheet (PS) boundary. The SAID electric field – the inherent part of the short-circuiting loop – stops the inward-moving MPF’s ions. In turn, SAPS are an integral part of the two-loop SCW system or SCW2L, where the downward (R2) current emerges in response to the upward (R1) current in the SCW’s “head”. The meridional Pedersen current, which connects the R1 and R2 currents, leads to SAPS -- the ultimate driver of the fast RC injections on the duskside.